Distribution and Conservation of Davilla (Dilleniaceae) in Brazilian Atlantic Forest Using Ecological Niche Modeling. (12th November 2014) - Martins Pereira, Ismael; Gomes-Klein, Vera Lúcia; Groppo, Milton
Abstract : We have modeled the ecological niche for 12 plant species belonging to the genus Davilla (Dilleniaceae) which occur in the Atlantic Forest of Brazil. This group includes endemic species lianas threatened by extinction and is therefore a useful indicator for forest areas requiring conservation. The aims are to compare the distribution and richness of species within the protected areas, assessing the degree of protection and gap analysis of reserves for this group. We used the Maxent algorithm with environmental and occurrence data, and produced geographic distribution maps. The results show that high species richness occurs in forest and coastal forest of Espírito Santo to Bahia states. The endemic species comprise D. flexuosa, D. macrocarpa, D. flexuosa, D. grandifolia, and D. sessilifolia . In the Atlantic Forest of southeastern Brazil, the following endemic species occur: D. tintinnabulata and D. glaziovii, with this latter species being included in the "red list" due habitat loss and predatory extractivism. The indicators of species richness in the coastal region of Bahia correspond with floristic inventories that point to this area having a high biodiversity. Although this region has several protected areas, there are gaps in reserves, which, combined with anthropogenic threats and fragmentation, have caused several problems for biodiversity.